Efeito de um programa de treinamento resistido e caminhada sobre a composição corporal, biomarcadores de saúde e funcionalidade em idosos - Munaro, Chiara (2024)
Aging is a continuous process accompanied by different changes that can compromise the autonomy and quality of life of elderly individuals. Physical exercise has been widely recommended, as it can reduce or mitigate the harmful effects on the health of this population. To investigate the effects of a resistance training (RT) and walking (W) program on body composition, health biomarkers and functionality after 12 weeks of training in elderly people. This is a test non randomized clinical trial, lasting 12 weeks. Forty-nine elderly people were allocated into three groups, resistance training group (RTG, n= 14); walking group (WG, n= 23) and control group (CG, n= 12). Sociodemographic information, anthropometric measurements, data on body composition, assessments of functional physical fitness were collected, in addition to blood samples being collected. Additionally, the SF-36 questionnaire was applied to assess quality of life. These procedures were conducted both at the beginning and at the end of the training period, allowing a pre- and post-intervention comparative analysis. It was observed that members of the Resistance Training Group (RTG) exhibited a significant increase in lower limb strength (from 10.5 ± 1.9 to 13.7 ± 2.6; p=0.001), a decrease in fasting glucose levels (from 96.2 ± 10.3 to 87.4 ± 6.4; p=0.016), and an improvement in the scores of most quality of life domains (p > 0.05). The Walking Group (WG) also showed improvements in lower limb strength (from 8.8 ± 1.7 to 12.6 ± 2.1; p=0.001). On the other hand, the Control Group (CG) showed an increase in lean mass (from 43 .6 ± 3.4 to 45.6 ± 4.0; p=0.002). The results found suggest that 12 weeks of RT and W promote improvements in muscle strength levels, but not in body composition and lipid profile in elderly people. These findings support the inclusion of RT in health programs for older adults, emphasizing its role not only in improving physical health but also in overall well-being.